Study of the mechanical properties of repair of AISI 1020 steels with a composite based on polymeric adhesive and carbon fiber - Silva, Felipe Roberto da Silva e; Martins, Silvana de Abreu; Filho, Arsitoclê Aguiar; Bernadá, Gabriel Mário Guerra; Martins, Charles de Abreu (Seven Editora, 2023)
Due to the great importance of steel in engineering and economics and the challenges related to its resistance to corrosion and high density, studying methods to extend its useful life becomes essential, avoiding failures in service or increased operational costs, like exchanging components, for example. Traditionally, in repairs of defects in steel, welding has been used. However, other methods have stood out, such as using adhesives and composites in repair, thanks to lower costs and greater operational ease. In this work, an experimental study of the repair of an AISI 1020 was carried out using a composite with structural adhesive based on epoxy and carbon fiber. A defect was caused in the machining laboratory through a 2mm hole in the entire thickness and a hole in half the thickness. A computer simulation was carried out to evaluate the effect and stress concentrations in the defect in AISI 1020 steel, which showed that the tensioned material begins to plasticize in the defect region. This confirmation was essential to validate the repair.Furthermore, after the repair, tensile tests were carried out to evaluate the repair effects. Previously, the blasting was used to improve the adhesion of the composite to the surface since roughness enhances the anchoring of the adhesive. After a tensile test, the positive effect of the repair was verified. DOI:https://doi.org/10.56238/interdiinovationscrese-081